Sistema de eletrocoagulação-flotação: uma unidade de tratamento de água inovadora para demandas eventuais e remotas do saneamento básico - Graepin, Cristiane (2020)
The need for an innovative, compact, portable and automated technology, originating from the operating sector of the sanitation companies, to meet the growing demand for water treatment, this study aimed to develop an electrochemical technology for the treatment of public water supply via electrolysis. The study was carried out in two stages: in stage I, the batch electrocoagulation-flotation (ECF) reactor was built, in discontinuous flow, to evaluate the effects of the variables that influence the ECF, in addition to determining an ideal operational configuration for the reactor. A 26-2 factorial design was carried out with 6 independent variables that could influence the treatment by ECF, namely: initial pH, electric current, electrolysis time, agitation, distance between electrodes and number of electrodes, followed by a central rotational composite design (DCCR) 24, with the variables: initial pH, electric current, electrolysis time and number of electrodes, and a DCCR (22), with the variables electric current and electrolysis time. In step II, a continuous flow ECF system was developed, through a central composite design 23, with the variables: current density, height of modules and flow. Followed by a DCCR (22), in which the operating flow and length of the helical tubular flocculator tubing variables were analyzed, and a DCCR (22) in which the initial pH and aluminum concentration were analyzed. In this stage, the ECF system was scaled from bench scale to pilot scale. The ideal treatment condition for the batch ECF reactor was as follows: distance between the electrodes of 1.0 cm, agitation of 280 rpm, initial pH 7.0, 4 units of electrodes, electrical current of 0.3A and time of 25 min electrolysis This condition promoted a color removal efficiency of 82.03 %, final pH of 8.51, mass consumption of electrodes of 0.05 kg m-3, sludge production of 0.19 kg m-3, consumption of energy of 0.45 kwh m-3 and residual aluminum of 7.48 mg L-1. For the ECF system continuous flow the ideal treatment condition was: current density of 1 mA cm-2, initial pH of 6.4, flow equal to or less than 0.8 L min-1, pipe length greater than 17 m, velocity gradient between 250-350 s-1 and 0.3 cm distance between the electrodes. The efficiency of water treatment in this condition was satisfactory, with a color removal greater than 85 %, turbidity greater than 80 % and total coliforms greater than 90 %, with an energy consumption of less than 0.04 kWh m-3, production of sludge less than 0.03 kg m-3 and residual aluminum concentration less than 1 mg L-1. The ECF system was installed on a pilot scale, and its performance monitoring was started, with different characteristics of raw water samples. However, it was possible to develop in this study an ECF system for the treatment of supply water, in an innovative, compact, portable, efficient and with automation potential.